Proyectos ambientales escolares en Instituciones Educativas del sector oficial en el Municipio de Santiago de Cali - Medina Agredo, Patricia (Universidad Santiago de Cali, 2017)
The following report presents the results of the research on the state of School Environmental Projects-PRAE, in some of the official educational institutions of commune 19 of the municipality of Santiago de Cali. Rather than verifying their existence or not, its purpose was to identify how contextualized the PRAE are in the design of the IEP of the selected educational institutions and how pertinent is their curricular proposal so that it becomes a contribution to the Growth and development of the community. For this purpose, the inter-view was used as a research technique and a survey was carried out in which the different phases of PRAE construction are addressed: contextualization, planning and implementation, applied to a sample of the educational com-munity made up of: managers, administrators, teachers, students and parents.